The reconstruction identity in people living with HIV in Nepal. - Aryal, Ram Prasad (2015)
ABSTRACT: This research is about the experiences of people living with HIV (PLHIV) in Nepal, especially with regard to the processes of reconstructing their identities. The processes of identity reconstruction include migration, concealing and disclosing HIV status, movement towards economic independence, gaining knowledge on Human Immuno deficiency Virus (HIV) and Acquired Immuno-deficiency Syndrome (AIDS), practising HIV treatment, receiving support of organizations, and practising spirituality. Despite the availability of some studies on HIV and AIDS in Nepal, most have focused on epidemiological facts. There is a dearth of Nepalese HIV and AIDS literature on identity reconstruction of PLHIV. This study investigated the lived experiences of 33 PLHIV related to their HIV stigma, discrimination and identity issues in Kathmandu and Pokhara valleys in Nepal, using semi-structured, face-to-face, in-depth interviews. The field data were analysed using a thematic, meaning-making approach. This research contributes to HIV literature by showing that the economic stigma and discrimination due to HIV experienced within a family are often stronger than social stigma and discrimination. This research proposes a model entitled "the reconstruction of identity in PLHIV in Nepal", based on the data derived in an inductive way from the two research sites, then moving from data to theory. There are various stages of identity ranging from spoiled to reconstructed. This proposed identity model is based on the economic and social empowerment of the PLHIV, together with identity transformation from one stage to another, and the situations participants experience in the contemporary Nepalese socio-political context. The identity of PLHIV is fluid and non-linear. This research suggests that access to resources often determines the degree of family and social stigma and discrimination. Moreover, PLHIV also reunite with both family and society after becoming economically independent and socially empowered. Indeed, HIV has been a catalyst, especially for in-migrant women with limited access to resources. This study has significant policy implications for improving the quality of life for PLHIV, reducing family and social stigma and discrimination as well as reconstructing their identity in Nepal, and in South Asian countries with similar socio-cultural and economic settings.